THE DEVELOPMENT OF PERSONAL LEARNING ENVIRONMENTS IN HIGHER EDUCATION Promoting Culturally Responsive Teaching and Learner Autonomy - Sun, Yilin; Xu, Xiaoshu (Routledge, 2024)
The Development of Personal Learning Environments in Higher Education explores how today's knowledge-based, learner-centered virtual platforms, which often limit teaching to a complimentary facilitation role, can compromise with the requirements and regulations of colleges and universities. Personal Learning Environments (PLEs) driven by culturally responsive teaching and learner autonomy represent a shift in the higher education paradigm, but how can scholars, designers, administrators, and faculty ensure effective, institutionally compatible construction and management of these systems? This book offers forward-thinking insights into the variety of student-centered learning interactions, particularly culturally and linguistically responsive pedagogies, that can be integrated into PLEs. Attending to quality assessment rubrics, the nuances of stakeholders' needs, and theoretically sound frameworks, these cross-cultural, interdisciplinary chapters explore how leaders, instructors, technologists, and learners can form a precise yet flexible ecosystem to fully realize PLEs in which co-created, intercultural narratives yield rich, relevant digital learning experiences.